A new record of Vaucheria incurva (Vaucheriaceae, Xanthophyceae), an extremely rare species, with taxonomic remarks on other Vaucheriae having disintegrated gametangial walls - Vishnyakov, Vasily S. (Phytotaxa, 2023)
N/A